Projects in linguistics and language studies : a practical guide to researching language - Wray, Alison; Bloomer, Aileen, 1947-; Wray, Alison (London : Hodder Education, 2012)
Projects in Linguistics and Language Studies, Third Edition, is your essential guide when embarking on a research project in linguistics or English language. This third edition is clearly divided into the subject areas that most appeal to you as a student: psycholinguistics; first- and second-language acquisition; structure and meaning; sociolinguistics; language and gender; accents and dialects; and the history of English. New to this edition is a chapter on computer-mediated communication (CMC), to help you get to grips with how the latest technology can make your project even more of a success. This third edition of Projects in Linguistics and Language Studies offers you practical advice on: Identifying a topic ; Making your background reading even more effective -planning and designing a project ; Collecting and analysing data ; Writing up and presenting your findings. With over 320 project ideas that you can use directly or adapt to suit different contexts and interests, and with chapters on how to reference effectively and how to avoid plagiarism, this third edition of Projects in Linguistics and Language Studies is a reference guide that you will use again and again during your studies.
Introduction: starting on the right foot -- Psycholinguistics -- First-language acquisition and development -- Second-language acquisition -- Structure and meaning -- Style in spoken and written texts -- Sociolinguistics -- Language and gender -- Accents and dialects of English -- History of English -- Computer-mediated communication -- Audio- and video-recorded data -- Experiments -- Questionnaires, interviews, and focus groups -- Observation and case studies -- Ethical considerations in research projects -- Transcribing speech phonetically and phonemically -- Transcribing speech orthographically -- Using computers to study texts -- Statistics and your project -- How to reference -- Plagiarism and how to avoid it -- Handy hints on writing good academic English -- Hints on giving a good oral presentation.
Previous ed.: published as Projects in linguistics. 2006.
Includes bibliographical references (p. [277]-299) and index.
Keywords: Linguistics -- Research -- Methodology